Effect of External Ankle Support on Ankle and Knee Biomechanics During the Cutting Maneuver in Basketball Players. (March 2017) - Klem, Nardia-Rose; Wild, Catherine Y.; Williams, Sian A.; Ng, Leo
Background: Despite the high prevalence of lower extremity injuries in female basketball players as well as a high proportion of athletes who wear ankle braces, there is a paucity of research pertaining to the effects of ankle bracing on ankle and knee biomechanics during basketball-specific tasks. Purpose: To compare the effects of a lace-up brace (ASO), a hinged brace (Active T2), and no ankle bracing (control) on ankle and knee joint kinematics and joint reaction forces in female basketball athletes during a cutting maneuver. Study Design: Controlled laboratory study. Methods: Twenty healthy, semi-elite female basketball players performed a cutting task under both ankle brace conditions (lace-up ankle brace and hinged ankle brace) and a no-brace condition. The 3-dimensional kinematics of the ankle and knee during the cutting maneuver were measured with an 18-camera motion analysis system (250 Hz), and ground-reaction force data were collected by use of a multichannel force plate (2000 Hz) to quantify ankle and knee joint reaction forces. Conditions were randomized using a block randomization method. Results: Compared with the control condition, the hinged ankle brace significantly restricted peak ankle inversion (mean difference, 1.7°; P = .023). No significant difference was found between the lace-up brace and the control condition ( P = .865). Compared with the lace-up brace, the hinged brace significantly reduced ankle and knee joint compressive forces at the time of peak ankle dorsiflexion (mean difference, 1.5 N/kg [ P = .018] and 1.4 N/kg [ P = .013], respectively). Additionally, the hinged ankle brace significantly reduced knee anterior shear forces compared with the lace-up brace both during the deceleration phase and at peak ankle dorsiflexion (mean difference, 0.8 N/kg [ P = .018] and 0.9 N/kg [ P = .011], respectively). Conclusion: The hinged ankle brace significantly reduced ankle inversion compared with the no-brace condition and reduced ankle and knee joint forces compared with the lace-up brace in a female basketball population during a cutting task. Compared with the lace-up brace, the hinged brace may be a better choice of prophylactic ankle support for female basketball players from a biomechanical perspective. However, both braces increased knee internal rotation and knee abduction angles, which may be problematic for a population that already has a high prevalence of knee injuries.